Improving Descriptive Writing Ability by Using Think-Talk-Write (TTW) Strategy - Mulyarti, Mulyarti; Rajab, Abd. (Universitas Muhammadiyah Barru, 2025)
This study examines how the Think-Talk-Write (TTW) strategy enhances students' abilities in descriptive writing. This study utilized a pre-experimental research design featuring a one-group pre-test and post-test approach, involving a total of 21 participants. The main tool for data collection was a writing test that evaluated five key components: organization, punctuation, grammar, vocabulary, and content. The findings revealed that the average score before the test was 65.65, which falls into the poor category, whereas the average score after the test rose to 81.67, placing it in the good category. The pre-test exhibited a standard deviation of 4.37, while the post-test demonstrated a standard deviation of 5.68. The analysis conducted using a paired t-test yielded a t-value of 5.09, surpassing the critical t-table value of 2.021 at a significance level of 0.05, thereby indicating a statistically significant enhancement in students’ writing performance. The results indicate that the TTW strategy serves as a potent instructional method that boosts student engagement and fosters the growth of writing abilities. Consequently, it is advisable for educators to integrate the TTW strategy as an alternative approach in writing instruction to enhance student engagement in text creation and elevate their overall writing skills.